INTERNATIONAL FINANCIAL INVESTMENTS AS CIVIL SOCIETY DEVELOPMENT SUPPORTING TOOL - Polyanska , A. S.; Kochkodan , V. B. (The actual problems of regional economy development, 2020)
The article examines the features of attracting international financial investment as civil society development supporting tool. In conditions of limited state and regional financing, the role of external financing is growing, the source of which is the financial market of foreign countries. The urgency of involving international financial and investment instruments in civil society development and the expediency of using EU best practices to implement the values of such development based on the Association Agreement with the EU are substantiated. The preconditions for the financial and investment instruments formation have been generalized. The content of financial and investment instruments as a source for development processes investment support is defined and the relationship between the financial market and the investment process as a prerequisite for the international financial and investment instruments formation of the civil society development support is outlined. The project activity is highlighted as a relevant investment technology in modern conditions, in particular through the financial instruments of the European Union (EU) and the main stages of the project idea implementation are described with regard to the civil society development. In general, the activities related to the international financial investment attracting into supporting of the citizens' desire to direct their own initiative to implement the values inherent in the community and relevant to civil society, include identifying problems that prevent investment attraction, analysis of available investment opportunities to address these problems, selection of target groups interested in solving the problem, identification of activities to improve the situation, preparation of the relevant project application and its submission for participation in the relevant international financial instrument, and in case of approval - implementation of all actions envisaged in the project and obtaining declared results and expectations.